The effectiveness of sago liquid waste as nutrient of Chlorella sp. culture in the peat water media - Fernandiaz, Revi; Harahap, Sampe (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Sago liquid waste is rich in micro and macro nutrient that can be used for growing Chlorella sp. To understand the effectiveness of the waste as a nutrient source to grow Chlorella sp., a study was conducted from November – December 2016. Different amount of sago liquid waste was added to 3L of peat water, they were P0(0%), P1(5%), P2(15%) and P3 (25%) of peat water volume. The Chlorella sp. was culture for 11 days. Parameters measured were the abundance and biomass of Chlorella sp., nitrate and phosphate concentration, dissolved oxygen, pH and temperature. Results shown that the best growth of Chlorella sp. was in the P1(5%), the abundance was 2,768,000 cells/ml and the biomass was 0.28 g/L. During the research, the nitrate and phosphate concentration reduced, from 0.5575 to 0.2540 mg/L and from 0.9358 to 0.3142 mg/L respectively. This fact indicates that the nutrients have been used for Chlorella sp. growth. Based on data obtained, it can be concluded that the sago liquid waste can be used as nutrient source for growth Chlorella sp. Keywords : Sago liquid waste, nutrient, growth, Chlorella sp.